Expression, purification and functional validation of a cancer-associated isoform of the HBx protein from human hepatitis B virus - Clavier, Alexis; Gómez-Evain, Santiago; Shida, Toshinobu; Abanti, Rubaba R.; Hammerstein, Franziska; Kielkowski, Pavel; Leuthold, Mila; Schütz, Anne (Protein expression and purification, 2026)
The human hepatitis B virus (HBV) causes hepatitis B, a liver infection that can be acute or chronic. HBV encodes four proteins, among which the X protein (HBx) plays a critical role in viral replication. During chronic HBV infection, in which the viral DNA is integrated into the host genome, the HBx1-120 isoform, comprising the N-terminal 120 residues, is highly expressed. Here, we describe a protocol for the recombinant overexpression and purification of untagged HBx1-120 from bacterial cells. The procedure is compatible with stable isotope labelling in minimal media. Following cell lysis, HBx1-120 was recovered from inclusion bodies (IBs), solubilized in urea, and purified by ion-exchange (IEX) and size-exclusion chromatography (SEC). The purified protein was extensively characterized, including by mass spectrometry and nuclear magnetic resonance (NMR) spectroscopy. Functionality was confirmed by a pulldown assay with a known interacting partner, Spindlin1. This protocol provides a robust framework to obtain untagged HBx1-120 for structural and functional in vitro studies.
Online verfügbar: 03. November 2025, Artikelversion: 05. November 2025
Gesehen am 13.02.2026